Blocking the Energy Loss of Dexter Energy Transfer in Hyperfluorescence OLEDs Via One‐Step Phenyl‐Fluorene Substitution of TADF Assistant Host. Issue 17 (9th June 2022) - Xie, Wentao; Peng, Xiaomeng; Li, Mengke; Qiu, Weidong; Li, Wei; Gu, Qing; Jiao, Yihang; Chen, Zijian; Gan, Yiyang; Liu, Kun kun; Su, Shi‐Jian
Abstract: Generally, the charge transfer character of thermally activated delayed fluorescence (TADF) materials results in a long excitonic lifetime and broad‐band emission. With the combination of unity exciton utilization of TADF material and high radiative rate and narrow‐band emission of conventional fluorescence (CF) dopant, hyperfluorescence organic light‐emitting diodes (HF‐OLEDs) attract extensive attention in industry and academia recently. Till now, Dexter energy transfer (DET) from the triplet state of TADF assistant host to the dark triplet state of CF guest is the top‐drawer energy loss issue root in HF‐OLEDs. Herein, the energy loss of DET is blocked through one‐step substitution of TADF assistant host by electronically inert phenyl‐fluorene terminal for the first time. The blocking effect on DET process in HF‐OLEDs is investigated by means of photophysical characterization, theoretical calculation, device fabrication, and Monte Carlo simulation. The maximum external quantum efficiency of 18.1% with Commission Internationale de L'Eclairage coordinates of (0.61, 0.38) is achieved, which is on par with the state‐of‐the‐art efficiency for red HF‐OLEDs. This work presents a feasible design strategy for TADF assistant host aimed at achieving highly efficient HF‐OLEDs with narrow‐band emission. Abstract : The triplet energy loss of Dexter energy transfer for red hyperfluorescence device was blocked through one‐step substitution of thermally activated delayed fluorescence sensitizer by electronically inert phenyl‐fluorene terminal, giving a proof‐of‐concept device with a maximum external quantum efficiency of 18.1% and Commission Internationale de L'Eclairage coordinates of (0.61, 0.38).